Semi-/empirical transition prediction and application to an isolated rotor in hover. (1st January 2012) - Heister, C.C.
The transition prediction capability of two semi-/empirical criteria originating from fixed wing applications is studied for steady, rotary wing application. This includes the AHD criterion, and two variants of the Michel criterion. Both criteria are used with approximated boundary layer data for improved numerical robustness of the prediction algorithm in an industrial context. The transition criteria have been implemented in the structured flow solver FLOWer of the German Aerospace Center (DLR). A two-dimensional airfoil test case (Somers NLF(1)-0416) is used to study the prediction accuracy of the criteria, comparing three different one and two equation turbulence models. A three-dimensional rotor test case at hover (DLR Bo 105 flight test) serves to validate the computed transition locations. A relative comparison of the predicted rotor efficiency illustrates the differences in performance prediction between the AHD and the Michel criterion.